ANALYSIS OF HIGHER ORDER AND THINKING SKILLS (HOTS) ON LEARNING ASSESSMENT INSTRUMENTS STUDENTS OF THE TEACHER PROFESSIONAL PROGRAM (PPG) DALJAB I - Ermawati; Setuju (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
This study describes an assessment instrument based on Higher-Order and Thinking Skills (HOTS) made by students of the Teacher Profession Program (PPG) Daljab I batch 2021. This research is a descriptive study. The population of this study was 34 students of Daljab I Group I batch 2021, Universitas Sarjanawiyata Tamansiswa Yogyakarta. The research sample consisted of 9 students from the DIY Province. The data and data sources used are assessment instruments (questions) that are compiled while students are taking PPG and have been uploaded in the form of Learning Tools III. The data analysis technique uses Miles and Huberman's interactive analysis which includes data reduction, data presentation, and drawing conclusions or verification. The results show that from 9 samples, 96 questions were obtained. Of the 96 items, 65 questions are HOTS (68.8%) and 31 questions are not HOTS (32.2%). The instrument questions that were made did not meet the HOTS due to the following reasons. 1) Questions that have not been HOTS are still below C3. 2) Some questions do not use a stimulus, but there are some HOTS questions that use a stimulus in the form of discourse, stories, and pictures; 2) Some questions have not been taken from the context of the real world/daily life; 3) some of the questions given do not contain critical, logical, metacognitive, and creative thinking processes. 4) Some of the questions have not applied the rules for multiple choice/explanation/filling questions.